2011
DOI: 10.1093/bja/aer007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the nociceptin precursor and nociceptin receptor is modulated in cancer and septic patients

Abstract: NOP and pN/OFQ expression in peripheral blood cells was modulated in end-stage cancer and septic patients compared with healthy controls, whereas changes in postoperative patients were minor. The involvement of the NOP-pN/OFQ system in inflammation, impaired immune function, and pain has to be further elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…For HPRT, 16 nM of universal probe #73 (Roche, Mannheim, Germany), 4 µl LightCycler® TaqMan® Master (Roche, Mannheim, Germany) and 10 pmol of each primer (TIB MOLBIOL, Berlin, Germany) were used. The sequence of primers and PCR conditions have been described previously [7], [10], [19]. Primer sequences were as follows: HPRT, 5′-TGACCTTGATTTATTTTGCATACC-3′ and 5′-CGAGCAAGACGTTCAGTCCT-3′; NOP, 5′-TGCCGTTCTGGGAGGTTATCTA-3′ and 5′-TTAGGGTGAAGGTGCTGGTGA-3′; PNoc, 5′-CCTGCACCAGAATGGTAATG-3′ and 5′-GCTGAGCACATGCTGTTTG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…For HPRT, 16 nM of universal probe #73 (Roche, Mannheim, Germany), 4 µl LightCycler® TaqMan® Master (Roche, Mannheim, Germany) and 10 pmol of each primer (TIB MOLBIOL, Berlin, Germany) were used. The sequence of primers and PCR conditions have been described previously [7], [10], [19]. Primer sequences were as follows: HPRT, 5′-TGACCTTGATTTATTTTGCATACC-3′ and 5′-CGAGCAAGACGTTCAGTCCT-3′; NOP, 5′-TGCCGTTCTGGGAGGTTATCTA-3′ and 5′-TTAGGGTGAAGGTGCTGGTGA-3′; PNoc, 5′-CCTGCACCAGAATGGTAATG-3′ and 5′-GCTGAGCACATGCTGTTTG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Stamer et al (23) found lower pN/OFQ expression in the peripheral blood cells (PBC) of end-stage cancer patients and septic patients compared with healthy controls. They also showed that increased plasma procalcitonin, a marker of infl ammation, was associated with decreased pN/OFQ in all patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, when evaluating the role of N/OFQ-NOP receptor system in a complex event such as sepsis, we should be aware of the broad range of effects evoked by NOP receptor signaling, that contribute to the septic condition, such as impairment of cardiovascular performance and tissue perfusion, beside the immune responses herein discussed (for a review see [57]). Very recently, Stamer and colleagues [58] have shown that peripheral blood cells from patients with sepsis had higher N/OFQ and lower ppN/OFQ mRNA expression than healthy controls. Again, these observations suggest the involvement of the NOP-N/OFQ system in inflammation and impaired immune function in sepsis.…”
Section: N/ofq-nop Receptor System and Inflammatory And Autoimmunementioning
confidence: 99%
“…Anton and colleagues [43] showed that N/OFQ inhibits antibody formation in a naloxone-insensitive manner, thus suggesting that N/OFQ effects, at least in this particular case, are not mediated by classical opioid receptors [43]. Another recent evidence that show no interaction between N/OFQ-NOP receptor system and the classic opioid system is coming from a clinical study, in which patients suffering from cancer who were taking opioid medication (morphine or equivalents) did not display any significant alterations in NOP and ppN/OFQ expression compared with those who did not receive opioids pretreatment [58]. These observations suggest that, despite the immunosuppressive effects of opioid in addicted patients [110], the mechanisms by which classical opioids affect immune functions, especially in the periphery, did not seem to be related to the N/OFQ-NOP receptor system.…”
Section: Relationship Between N/ofq and Classical Opioids In The Rmentioning
confidence: 99%